The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/mpg.0b013e318255117b
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole‐induced Myositis in a Child Receiving Triple Therapy for Helicobacter pylori Infection

Abstract: How Often Do You Fail to Take All of Your Medication?T o the Editor: We read with interest the article by Prieto-Jimenez et al (1); however, the conclusion overlooks the problem of adherence to treatment. A success rate of 44% has never been reported since dual therapies were introduced or in more recent pediatric trials. Compliance is the most important factor predicting treatment success (2), and eradication rates of 20% were reported in those taking <60% of pills (3).In the El Paso children, several indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Visruthan et al 13 reported a case of a 12-year-old Chinese male patient who was started on a 14-day course of triple therapy for eradication of Helicobacter pylori . Treatment included omeprazole 20 mg twice daily, amoxicillin 500 mg twice daily, and clarithromycin 500 mg twice daily.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Visruthan et al 13 reported a case of a 12-year-old Chinese male patient who was started on a 14-day course of triple therapy for eradication of Helicobacter pylori . Treatment included omeprazole 20 mg twice daily, amoxicillin 500 mg twice daily, and clarithromycin 500 mg twice daily.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors conclude that PPIs should be recognized as having the potential for this rare adverse effect, especially in children reciving triple therapy with concomitant use of clarithromycin. 13…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The drugs that the patient had been exposed to before the onset of myositis were reviewed and myositis might also be related to daptomycin, omeprazole or allopurinol. [6][7][8] While their participation cannot be definitively excluded, the three of them usually present with elevated CK levels, with or without muscle symptoms while our patient presented with serum CK within normal range despite muscle pain and swelling. In addition, our patient had previously been exposed to omeprazole without having observed any side effects.…”
Section: Discussionmentioning
confidence: 75%
“…From this evidences omeprazole is the primary candidate that induced myopathy. In addition, there were 16 case reports in the literature and summarized in a case series that associate the use of omeprazole with myopathy . Among these 16 cases, two were identified as Asians, but race was not reported among the other cases.…”
Section: Discussionmentioning
confidence: 99%